2018
DOI: 10.3390/ijms19092655
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Analysis Reveals Non-Controlled Activation of Photosynthesis and Protein Synthesis in a Rice npp1 Mutant under High Temperature and Elevated CO2 Conditions

Abstract: Rice nucleotide pyrophosphatase/phosphodiesterase 1 (NPP1) catalyzes the hydrolytic breakdown of the pyrophosphate and phosphodiester bonds of a number of nucleotides including ADP-glucose and ATP. Under high temperature and elevated CO2 conditions (HT + ECO2), the npp1 knockout rice mutant displayed rapid growth and high starch content phenotypes, indicating that NPP1 exerts a negative effect on starch accumulation and growth. To gain further insight into the mechanisms involved in the NPP1 downregulation ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 75 publications
(93 reference statements)
2
9
0
Order By: Relevance
“…Similar effects are observed under nutrient starvation, including Mg 2+ and Fe 2+ , which are essential co-factors for several redox-active proteins in the photosynthetic ETC. More recently, Inomata et al (2018) reported the chloroplast phosphoproteome profile of a rice nucleotide pyrophosphatase / phosphodiesterase 1 (NPP1) mutant. This study highlighted that the loss-of-function of NPP1 in rice leaves increased stomatal conductance, photosynthesis, starch, and sucrose storage while also impacting proteins involved in carbohydrate metabolism and protein synthesis system under high temperature and CO 2 conditions.…”
Section: “-Omics” Analyses To Identify Novel Targets and Network Undmentioning
confidence: 99%
“…Similar effects are observed under nutrient starvation, including Mg 2+ and Fe 2+ , which are essential co-factors for several redox-active proteins in the photosynthetic ETC. More recently, Inomata et al (2018) reported the chloroplast phosphoproteome profile of a rice nucleotide pyrophosphatase / phosphodiesterase 1 (NPP1) mutant. This study highlighted that the loss-of-function of NPP1 in rice leaves increased stomatal conductance, photosynthesis, starch, and sucrose storage while also impacting proteins involved in carbohydrate metabolism and protein synthesis system under high temperature and CO 2 conditions.…”
Section: “-Omics” Analyses To Identify Novel Targets and Network Undmentioning
confidence: 99%
“…Intact chloroplasts were purified from seedlings grown in a light condition using the Percoll (GE Healthcare) density-gradient centrifugation method, as described earlier [45,46] and analyzed by SDS-PAGE and immunoblotting. Proteins were extracted from brown rice seed (harvested in the field), calli (cultured in a dedifferentiation medium for four weeks), shoot (germinated at 30 • C for seven days in the dark and moved to a growth chamber (28:23 • C, 12:12 h, light:dark; 20,000 lux) for three days), and mature leaves (germinated at 30 • C for seven days in the dark and moved to a growth chamber (28:23 • C, 12:12 h, light:dark; 20,000 lux) for eight days).…”
Section: Protein Extraction and Immunoblotting Analysismentioning
confidence: 99%
“…Interestingly, non-controlled activation of protein translation and photosynthesis has been revealed by proteomic investigations in a rice npp1 mutant under conditions of elevated temperature and carbon dioxide [35]. In the npp1 mutants, increased expression of several 14-3-3 proteins was noted, indicating that the NPP1 gene disruption can alter protein phosphorylation status.…”
Section: Strategies Of Plant Biotechnology To Meet the Increasing Demmentioning
confidence: 99%